Health facility planning and healthcare architecture: the conflict and the advantage in project implementation towards clarifying the role of architects and health facility planners –for better project delivery- the Malaysian experience - Mohd Nawawi, Norwina; Khalid, Aisyah; Ahmad Shazali, Shafinaz (2013)
The use of effective human resource by virtue of training and experience is implicit for a planned success of any project. In healthcare projects, where capital and operating cost is paramount; implementation time is intensive and lengthy; as well as the stake holders are of varied backgrounds and expectations; coordination is very important. Although healthcare projects require a multi-disciplinary participation, the architect, as lead consultant is still the responsible person in whole set-up. The paper thus focuses on the role of architects in healthcare projects and the so-called “medical planner” as the health facility planner in the Malaysian implementation of public healthcare projects, with the objective of reviewing the current practice and proposes a clearer role for the two "professions" towards a betterment of the project as a "green and sustainable working relation". Both qualitative and quantitative method are adopted for this study with primary data collected through interviews, questionnaire and experiences of current and past projects; whilst secondary data collected through content analysis of literatures. The scope of the study is confined to the two roles of the profession i.e. architect and health facility planner. The study limitations are available time and availability of unrestricted documents as evidence. Significance of these findings would be a contribution in deriving and clarifying the respective roles of the two professions for the industry to adopt as consultancy job scope guidelines and responsibility.